Use and tolerability of a side pole static ankle foot orthosis in children with neurological disorders. (April 2017) - Delvert, Céline; Rippert, Pascal; Margirier, Françoise; Vadot, Jean-Pierre; Bérard, Carole; Poirot, Isabelle; Vuillerot, Carole
Background: Transverse-plane foot deformities are a frequently encountered issue in children with neurological disorders. They are the source of many symptoms, such as pain and walking difficulties, making their prevention very important. Objectives: We aim to describe the use and tolerability of a side pole static ankle foot orthosis used to prevent transverse-plane foot deformities in children with neurologic disorders. Study design: Monocentric, retrospective, observational study. Methods: Medical data were collected from 103 children with transverse-plane foot deformities in one or both feet caused by a neurological impairment. All children were braced between 2001 and 2010. Results: Unilateral orthosis was prescribed for 32 children and bilateral orthosis for 71. Transverse-plane foot deformities were varus in 66% of the cases and an equinus was associated in 59.2% of the cases. Mean age for the first prescription was 8.6 years. For the 23 patients present at the 4-year visit, 84.8% still wore the orthosis daily, and 64.7% wore the orthosis more than 6 h per day. The rate of permanent discontinuation of wearing the orthosis was 14.7%. Conclusion: The side pole static ankle foot orthosis is well tolerated with very few side effects, which promotes regular wearing and observance. Clinical relevance: Side pole static ankle foot orthoses are well tolerated and can be safely used for children with foot abnormalities in the frontal plane that have a neurological pathology origin.